Modified sonoelastographic scale score for lymph node assessment in lymphoma – a preliminary report - Łasecki, Mateusz (J Ultrason, 2015)
Elastography is a new method of assessment of lymph node consistency. The majority of papers focus on metastases detection of head and neck or breast tumors. The typical desmoplastic reaction in connective tissue stroma in cancer, which is responsible for tissue's hardening, is seen in lymphoma less frequently. MATERIAL AND METHODS: Study of 15 patients with active Hodgkin and non-Hodgkin lymphomas and 16 previously treated patients with no evidence of recurrence. A total of 60 patients suffering from reactive lymphadenopathy was the control group. The size, appearance, vascularity and elastogram of lymph node was analyzed. RESULTS: Type C elastogram correlated strongly with lymph nodes which presented at least three pathologic features in 2D image. Large lymph nodes with long axis diameter over 3 cm may have ‘cheese with holes’ appearance rather than common type C elastogram. CONCLUSION: According to our simplified sonoelastography scoring system, type C elastogram was present mainly in patients with active lymphoma affecting lymph nodes, which showed all four features that we analyzed using conventional ultrasonography. This elastogram was also present in reactive lymphadenopathies. Distinctive for large lymph nodes in patients with active forms of lymphoma “cheese with holes” appearance, can be considered as equal with type C image, although it is corresponding to type B sonoelastographic map.